PERLINDUNGAN HUKUM BAGI PIHAK KETIGA TERHADAP AKTA PERJANJIAN PERKAWINAN YANG DIBUAT SELAMA DALAM IKATAN PERKAWINAN (STUDI AKTA PERJANJIAN PERKAWINAN NOMOR 76 TERTANGGAL 21 JULI 2022) - Siregar, Sausan Raihanah; Devi, Tengku Keizerina; Sembiring, Idha Aprilyana; Tony, Tony (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2024)
Before the Constitutional Court decision Number 69/PUU-XIII/2015, prenuptial agreements were only made at the time or before the marriage took place. However, after the issuance of the Constitutional Court decision Number 69/PUU-XIII/2015, Article 29 paragraph (1) prenuptial agreements no longer had to be made before or on the day of the marriage, but rather, married couples can create a prenuptial agreement while in the marital bond. This study discusses the obligations of a Notary in performing their duties regarding the request to create a Prenuptial Agreement by a married couple related to third parties, the status of the assets of the married couple who made the prenuptial agreement in deed number 76 dated July 21, 2022, concerning the guarantee of debt to third parties, and legal protection for third parties in the Prenuptial Agreement made before the Notary based on Prenuptial Agreement Deed Number 76 dated July 21, 2022. The method used in this research is a normative juridical method with a descriptive-analytical nature. The type of data used is secondary data consisting of primary, secondary, and tertiary legal materials. The data collection techniques include literature study and interviews. The collected data is then analyzed qualitatively to obtain descriptive-analytical results. The results of this study indicate that: 1) The obligations of a Notary in performing their duties regarding the request to create a Prenuptial Agreement by a married couple related to third parties involve creating the prenuptial agreement in an authentic form and validating the prenuptial agreement made by the parties under private hand and signed by the parties in accordance with Article 15 paragraph (1) of the Notary Office Law. 2) The status of the assets of the married couple who made the prenuptial agreement in deed number 76 dated July 21, 2022, concerning the guarantee of debt to third parties, does not apply retroactively (change). 3) Legal protection for third parties with the creation of Prenuptial Agreement Deed Number 76 dated July 21, 2022, made before the Notary, is that the personal assets of each spouse who enters into an agreement with the third party remain.